2019
DOI: 10.1093/mnras/stz3220
|View full text |Cite
|
Sign up to set email alerts
|

Stellar dynamos with solar and antisolar differential rotations: Implications to magnetic cycles of slowly rotating stars

Abstract: Simulations of magnetohydrodynamics convection in slowly rotating stars predict antisolar differential rotation (DR) in which the equator rotates slower than poles. This anti-solar DR in the usual αΩ dynamo model does not produce polarity reversal. Thus, the features of large-scale magnetic fields in slowly rotating stars are expected to be different than stars having solar-like DR. In this study, we perform mean-field kinematic dynamo modelling of different stars at different rotation periods. We consider ant… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 79 publications
2
18
1
Order By: Relevance
“…The indication of tilt quenching as seen in Figure 4(a) gives an observation support of the following nonlinear quenching in the Babcock-Leighton α or in γ 0 routinely used to saturate the magnetic field growth in kinematic dynamo models (e.g., Choudhuri et al 1995;Dikpati & Charbonneau 1999;Chatterjee et al 2004;Karak et al 2019).…”
Section: Magnetic Quenching Of Tilt Anglesupporting
confidence: 58%
“…The indication of tilt quenching as seen in Figure 4(a) gives an observation support of the following nonlinear quenching in the Babcock-Leighton α or in γ 0 routinely used to saturate the magnetic field growth in kinematic dynamo models (e.g., Choudhuri et al 1995;Dikpati & Charbonneau 1999;Chatterjee et al 2004;Karak et al 2019).…”
Section: Magnetic Quenching Of Tilt Anglesupporting
confidence: 58%
“…In this work, we have offered some speculation on how stars like the Sun may have evolved from the times they were born to the time when they reached an age beyond that of the present Sun. We expect that the Sun is shortly before changing its rotation from solar-like to antisolar-like differential rotation where the equator rotates slower than the poles; see also Karak et al (2019) for recent mean-field modeling of such stars. Stars with antisolar differential rotation are also potential candidates for displaying superflares (Katsova et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…We note that this anti-solar profile differs from the one used in Karak et al (2020). In this similar study using an α 2 Ω dynamo model, the value of the anti-solar coefficient Ω C /Ω Eq is kept at 0.93944 (as in the solar DR profile).…”
Section: Toroidal Magnetic Field Generationmentioning
confidence: 99%
“…Such models have been explored by Dubé & Charbonneau (2013) using mean-field coefficients extracted from 3D MHD prescriptions. Likewise, Karak et al (2020) have considered anti-solar models and found they could trigger magnetic cycles, but only with strong α-effect coupled with Ω-quenching. These authors obtained reversals in a α 2 Ω dynamo and argued that this could not be the case with classical kinematic αΩ models when considering a positive α-effect in the northern hemisphere.…”
Section: Introductionmentioning
confidence: 99%